PENGARUH PENERAPAN METODE SQ3R DISERTAI LEMBAR KEGIATAN SISWA (LKS) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 11 PADANG - Agusri, Melsa; Husna, Husna; Harisman, Yulyanti (STKIP PGRI Sumbar, 2013)
The research was by student compherension of math concept at still low in class VIII SMP Negeri 11 Padang. This matter is caused by activity read which is conducted by student in study less maximal as preparation learn and lack of active participation of student in study. This research aim to know what is compherension of math concept of student by applying method of SQ3R accompanied by Student Work Sheet (LKS) from at compherension of math concept of student by applying conventional study at class student of VIII SMP Country 11 Padang. This research type is research of experiment with device of random to subjek. Result of analysis of tes final at this research is obtained by data have homogeneous and normal distribution.Result of final tes of student conducted by hypothesis by obtaining P-value 0,010 and less than Â that is 0,05 so that raised to be hypothesis to be accepted by at trust level 95% that is compherension of math concept of student by applying method of SQ3R accompanied by Student Work Sheet (LKS) from at compherension of math concept of student by applying conventional study of class of VIII SMP Country 11 Padang.